Optimized Absorption Performance of FeSiCr Nanoparticles by Changing the Shape Anisotropy. Issue 23 (2nd November 2020) - Chen, Yang; Wang, Lei; Xiong, Houdong; Ur Rehman, Sajjad; Tan, Qiulan; Huang, Qingfang; Zhong, Zhenchen
Abstract : FeSiCr nanoparticles are prepared by plasma arc discharge and ball milling processes. After ball milling, the surface area and sizes of the FeSiCr nanoparticles become larger, and most of the nanoparticles become uneven. The increasing surface area and sizes of nanoparticles contribute to the electrical conductivity, enhance the space charge polarization between metal ions, and increase the shape anisotropy of FeSiCr nanoparticles. The inhomogeneity of nanoparticles reduces the activation energy ( Δ E ) of the FeSiCr nanoparticles. Therefore, the complex permittivity ( ε r ) is improved, and the impedance matching is optimized. The minimum reflection loss (RLmin ) of FeSiCr nanoparticles after ball milling for 6 h reaches −41.5 dB at 6.2 GHz and the effective absorbing bandwidth (RL < −10 dB) improves from 4.5 to 8.1 GHz ( d = 2.2 mm). The RLmin of FeSiCr nanoparticles after ball milling for 4 h is −40.1 dB at 6.9 GHz, which is slightly less than that of the sample after ball milling for 6 h, whereas the effective absorption bandwidth (RL < −10 dB) is from 5.8 to 9.0 GHz ( d = 2.2 mm). It shows that the absorption performance of FeSiCr nanoparticles can be improved by changing the shape anisotropy. Abstract : FeSiCr nanoparticles are prepared by plasma arc discharge and ball milling processes. The minimum reflection loss (RLmin ) of FeSiCr nanoparticles after ball milling for 6 h reaches −41.5 dB at 6.2 GHz and the effective absorbing bandwidth (RL < −10 dB) improves from 4.5 to 8.1 GHz ( d = 2.2 mm).